Imaginative resistance without conflict - Mahtani, A (2012)
I examine a range of popular solutions to the puzzle of imaginative resistance. According to each solution in this range, imaginative resistance occurs only when we are asked to imagine something that conflicts with what we believe. I show that imaginative resistance can occur without this sort of conflict, and so that every solution in the range under consideration fails. I end by suggesting a new explanation for imaginative resistance-the Import Solution-which succeeds where the other solutions considered fail. © 2010 Springer Science+Business Media B.V.